From Beauty to Identity: Cultural Value Betangas Tradition in Sambas Malay Society - Iwan Ramadhan; Muhammad Agus Hardiansyah; Yudhistira Oscar Olendo; Mualimin Mualimin; Indra Utama (Universitas Andalas, 2023)
The purpose this research is to determine the significance of the Betangas tradition's values, meanings, and processions among the Sambas Malay population in West Kalimantan province. The examine method used is a qualitative research method with a descriptive research type. The examine approach employed is qualitative using a descriptive study design. The Betangas tradition is generally carried out when there is a wedding celebration, especially in the Sambas area. The purpose of the Betangas tradition is being replaced by grooming equipment for the bride and groom when approaching the wedding. This is because Betangas have the goal of reducing excessive body odor and cleansing the body of both the bride and groom who will carry out the wedding and the special assumptions of the Sambas people. This study obtained results in the meaning of Betangas as a form of gratitude to Allah Subhanahu Wa Ta'alla for the Sambas Malay community, who are mostly Muslim and as a request for the two bride and groom to live a household life. While the function of the Betangas procession is to reduce sweating and cleanse the body's unpleasant odor caused by human sweat. Generally, the Betangas tradition is carried out for the bride and groom, but it is possible that anyone can carry out this tradition. The Betangas tradition is carried out from generation to generation and is still strong in the Sambas region in the Sambas Malay community as local wisdom that is still alive amidst the currents of globalization.